Modeling the influence of information technology (IT) adoption factors on the electronic voting (E-Voting) technology using partial least squares-structural equation model (PLS-SEM) methods - Salimonu, I.R.; Shiek Osman, Wan Rozaini; Shittu, A. J.K . (IEEE Nigeria, 2014)
Although there are many factors influencing the organizational adoption of information technology innovations, the lack of knowledge as to those that affect the adoption decision of Electronic Voting technology in the organizational context, especially from the perspectives and perceptions of developing countries remains fundamental and of necessity if such adoption decision is to succeed.This paper discusses the theoretical and empirical model that identifies the relevant determinants factors within the context of an electoral management organization that might influence Electronic Voting technology adoption in Nigeria.Six theoretical constructs derived from diffusion of innovations; technology-organization-environment; Iacovou et al. theories and other relevant literatures on organizational adoption of technology were identify and consider.The research instrument were validated in a survey of managerial and operational staff of the Independent National Electoral Commission of Nigerian and tested against the model using Partial Least squares Structural Equation Modeling-PLS-SEM method of data analysis.The predictive tendency of the factors is quiet substantial (84%) and represents higher variance in the adoption of Electronic Voting technology with good model fit. The study produced useful insights into the factors that influence organizational adoption of Electronic Voting technology and provided new ideas in the understanding of information technology innovation adoption in the organizational context.